(3GdLRA ef MOjK CHj Ydi GdMSf Hf YQags - (3GdMSf Hf YQaI Hf jRjO GdYHOj, CHh Ydjs
(3ChdgG (B:s
(3CNHQfG GdYHO GdabjQ Edi Gddg JYGdi GdGeGe GdYdGeI Jbi GdOjf GHh GdaVd eMeO Hf eMeO Hf CHj eMeO Hf agO GdgGTei Gdeci GdTGaYi SeGYkG Ydjg dLejYg ai YUQ jhe GdGMO NGeS YTQ ef Pi GdbYOg s
(3BNQgG (B:s
(3Yf YGFTI QVi Gddg YfgG Gf GHGHcQ QVi Gddg Yfg ONd Ydi GdfHi Udi Gddg Ydjg hSde HYO haGJg ahVY aGg Hjf Yjfjg hhVY jOjg Ydi UOZjg abGd hGfHjGg hGNdjdGg hGUajGg BNQ GdLRA hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HghGeTg MhGTi fbdJ ef NW GdMGaX GHf fGUQ GdOjf MGaX OeTbs
(3hYdgj NW GHf agO hSeGY hELGRI GdGNQjf s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(2000 801(2)) s
Keywords: (3GdMOjK h GdeUWdMs